Alexander and Aristotle on the ef cient causality of the soul - Mittelmann, Jorge (Estudios de Filosofía, 2009)
this essay holds that one of the most compelling challenges that a psychology which is Peripatetic in inspiration must face is to keep the causal relevance of the soul within the three orders of physical change (movement, alteration, and growth) without turning the soul into an inner ‘mover’ that displaces the organism on account of being in contact with it. If this hindrance is not solved, such a psychology could not assert that the soul is both an unextense and impassive item, but (at best) a subtle body displacing another baser body. This paper suggests a combined reading of Alexander’s and Aristotle’s treatise on the soul for the sake of presenting Alexander’s strategy as a successful manner of facing that plain dif culty. According to Mittelman, Alexander would nd in Aristotle’s ‘dispositional states’ the proper paradigm to conceive the causal ef cacy of forms. Such dispositional states could be unmoved movers insofar as they satisfy a double condition, which neither the Platonic Forms nor the subtle bodies can satisfy: on the one hand, their incorporeal character does not make them (separate) substances, on the other hand, their inseparable character does not turn them into bodies displacing other bodies on account of being in touch with them. In this fashion, the Aristotelian would gather all the explanatory advantages both of the Platonic and of the Stoic, avoiding at the same time their own inconveniences.